High relapse rate of T cell acute lymphoblastic leukemia in adults treated with Hyper‐CVAD chemotherapy in Sweden. (21st February 2014) - Kozlowski, Piotr; Åström, Maria; Ahlberg, Lucia; Bernell, Per; Hulegårdh, Erik; Hägglund, Hans; Karlsson, Karin; Markuszewska‐Kuczymska, Alicja; Tomaszewska‐Toporska, Beata; Smedmyr, Bengt; Amini, Rose‐Marie; Hallböök, Helene; et al.
Abstract Background Hyper‐CVAD is widely used to treat acute lymphoblastic leukemia (ALL) and aggressive lymphomas. This multicenter, population‐based study assessed the efficacy of Hyper‐CVAD as first‐line therapy in patients with T‐cell ALL (T‐ALL). Patients and methods Between October 2002 and September 2006, 24 patients were diagnosed with T‐ALL in Sweden; 19 were eligible for treatment with the protocol. Results The median age was 32 yr (range 18–72 yr). Complete remission (CR) was obtained in 17 of 19 (89%) patients, and the treatment was relatively well tolerated. Allogeneic stem cell transplantation (SCT) was recommended in high‐risk disease and was performed in four patients upfront. Two‐ and 5‐yr leukemia‐free survivals (LFS) in 17 patients with CR achievement were identical, at 29% (95% confidence interval [CI]: 8–51). Two‐ and 5‐yr overall survival (OS) in whole cohort was 63% (95% CI: 42–85) and 47% (95% CI: 26–69), respectively. The 5‐yr LFS for 15 patients who did not receive allogeneic SCT upfront were 20% (95% CI: 0–40), although 14 of 15 completed the protocol (eight cycles). Relapse occurred in 2 of 4 upfront‐transplanted patients and in 12 of 15 patients treated with chemotherapy alone, six of whom received allogeneic SCT in CR2. Age ≥35 yr influenced OS negatively in univariate analysis (HR 5.1, 95% CI: 1.55–16.7). Conclusions Hyper‐CVAD treatment resulted in a high CR rate and appeared safe, but it showed poor efficacy at preventing relapse. Therefore, this treatment is no longer recommended for adults with T‐ALL in Sweden.